Genetic predisposition in pancreatitis. Issue 5 (October 2018) - Gonska, Tanja
Abstract : Purpose of review: Genetic mutations are the primary cause for acute recurrent (ARP) and chronic pancreatitis in children. Further, our medical approach for many diseases is changing from a one-drug therapy to more individualized therapeutic strategies. In respect to the therapeutic management of ARP/chronic pancreatitis, this entails an understanding of the individual, mainly genetic, risk factors that led to pancreatitis disease. Recent findings: New pancreatitis-associated genes are continuously emerging from increasingly large genetic cohort studies. Furthermore, newer research findings demonstrate that multiple genetic and nongenetic factors are required to increase the individual risk for developing ARP/chronic pancreatitis. Last, there is new exciting development towards targeted pancreatitis therapy in the future. Summary: This review introduces the current concept of ARP/chronic pancreatitis as a complex disease caused by multiple genetic and nongenetic factors. This warrants careful evaluation of these patients and ideally consultation of a pancreas expert to help understand individual genetic risk profiles and to provide more effective patient consultation.